Development and application of an instrument to analyse pedagogical content interventions of ice hockey coaches - Wade, G.; Trudel, P.; Gaumond, S.; Larocque, L. (1999)
The purpose of this paper is to present the development and application of the Systematic Analysis of Pedagogical Content Interventions (SAPCI) instrument. The SAPCI allows researchers to record data on four components of a coach's pedagogical content interventions: 'What' (is the content), 'When' (is it transmitted), 'How' (is it transmitted) and 'Who' (is the receiver). In the first part of the paper the development of the instrument is discussed. An example of how the instrument can be applied is presented in the second part of the paper, using results from a three-year project with coaches of youth ice hockey. The paper concludes with suggestions for further refinement and application of the SAPCI instrument.